Efficient Removing of Pharmaceutical Contaminants of Commercial Carbamazepine by Natural Pyrite-Induced Fenton Reaction in a Wide pH Range - Tingting Shi; Jianjun Xi; Yidan Shao; Qiao Tong; Xi Zou; Hongping Zhou; Shourong Liu; Xiaoya Gao (Journal of Chemistry)
Pharmaceutical contaminants are causing great attention for the public people, urgently requiring to be eliminated from the environment. Herein, commercial pharmaceutical carbamazepine was chosen as a model to be degraded by a heterogeneous Fenton system using natural pyrite as catalyst. The catalyst was characterized by X-ray diffraction apparatus, high-resolution transmission electron microscopy, and X-ray photoelectron spectroscopy. The elements composition and chemical states of pyrite changed significantly after the Fenton reaction, which promoted the production of active species in the electron transfer process. The degradation efficiency of carbamazepine (2.5 mg/L) can reach 99.71% after 30 min with 0.3 g/L of pyrite and 5 mM of H2O2, respectively. The reaction system was suitable for a wide range of pH (3–9). The environmental adaptability examination of pyrite showed that humic acid (HA) had inhibitory effects on the degradation of carbamazepine. While the changes of degradation efficiency of carbamazepine were inconspicuous in the presence of NO3− and SO42−, indicating strong anti-interference to environment common anions. Free-radical capturers suggested that hydroxyl radical (∙OH), superoxide radical (∙O2−), and singlet oxygen (1O2) participated in the degradation of carbamazepine. This research has offered a new strategy of “treating wastes with wastes” to use pyrite to remove emerging pollutants.